Sliding behavior and wear mechanism of iron and cobalt-based high-temperature alloys against WC and SiC balls. (September 2016) - Huang, Changming; Zou, Bin; Guo, Peng; Liu, Yanan; Huang, Chuanzhen; Wang, Jun
Abstract: The sliding behaviors of two typical high-temperature alloys of GH2132 and GH605 against WC and SiC balls were investigated at environments from room temperature to 800 °C with a sliding speed of 50 to 125 m/min under a load of 10 to 20 N. The wear performances of high-temperature alloys, WC and SiC balls were rated and their mechanisms were discussed. The four sliding pairs exhibited the markedly different sliding behaviours, in which the GH2132/WC sliding pair had the maximum friction coefficient with 125 m/min under 10 N at room temperature. The variation trends of ball wear rates with the ambient temperature were at odds with those of friction coefficient. The higher friction coefficient did not always lead balls to suffer from the higher wear rate. The maximum worn depth approximated to 250 μm for the GH2132/WC sliding pair with higher friction coefficient. The GH605/WC sliding pair exhibited the lower friction coefficient and lower worn depth of plate. Whether at room temperature or high temperature, the GH605/SiC sliding pair significantly exhibited good wear resistance with a minor damage of ball and plate despite of its higher friction coefficient. Highlights: The GH2132 and GH605 exhibited opposite sliding behaviour. Higher friction coefficient did not always lead to higher wear rate of balls. Adhesion prevailed for all WC sliding pairs and adhesion was suppressed above 600 °C. GH605/SiC was predominated by abrasive wear due to oxides as a lubricant. GH605/SiC had good wear resistant with higher friction coefficient and less damage.